Recent benthic ostracoda in offshore sediment of Pulau Perhentian, Terengganu - Omar R.; Faiz N.N.; Yusoff M.N.A. (Penerbit Universiti Kebangsaan Malaysia, 2017)
A study on the distribution of recent benthic ostracoda in offshore sediment was carried out around Pulau Perhentian, Terengganu. A total of 10 sediment samples were taken from the sampling stations between latitude 5°55.228’ to 5°56.144’N and longitude 102°43.754’ to 102°44.850’E using a grab sampler of Petite Ponar type. The sediment samples were washed over 0.50 mm, 0.15 mm and 0.063 mm size sieves. The specimens were picked, identified and counted from dried samples. The species diversity, specimen abundance and the Shannon-Wiener’s diversity index, H’ was calculated using PAST software. The specimens were identified using Scanning Electron Microscopy (SEM) and Light Microscopy (LM). From this study, 43 species of ostracoda belonging to 16 families and 29 genera were identified. The dominant species is Hemicytheridea cancellata with 168 individuals obtained. The species diversity is ranged from 1 to 40 species and the abundance is from 1 to 269 specimens. The species diversity index, H’ is in the range of 0.69 to 3.21.